Exploring Factors Affecting Emergency Medical Services Staffs’ Decision about Transporting Medical Patients to Medical Facilities - Abbasali Ebrahimian; Hesam Seyedin; Roohangiz Jamshidi-Orak; Gholamreza Masoumi (Emergency Medicine International)
Transfer of patients in medical emergency situations is one of the most important missions of emergency medical service (EMS) staffs. So this study was performed to explore affecting factors in EMS staffs’ decision during transporting of patients in medical situations to medical facilities. The participants in this qualitative study consisted of 18 EMS staffs working in prehospital care facilities in Tehran, Iran. Data were gathered through semistructured interviews. The data were analyzed using a content analysis approach. The data analysis revealed the following theme: “degree of perceived risk in EMS staffs and their patients.” This theme consisted of two main categories: (1) patient’s condition’ and (2) the context of the EMS mission’. The patent’s condition category emerged from “physical health statuses,” “socioeconomic statuses,” and “cultural background” subcategories. The context of the EMS mission also emerged from two subcategories of “characteristics of the mission” and EMS staffs characteristics’. EMS system managers can consider adequate technical, informational, financial, educational, and emotional supports to facilitate the decision making of their staffs. Also, development of an effective and user-friendly checklist and scoring system was recommended for quick and easy recognition of patients’ needs for transportation in a prehospital situation.